Effect of hexavalent chromium on growth performance and metabolism in broiler chicken - Zhuo, Guorong; Wang, Lei; Ali, Muhammad; Jing, Zheng; Hassan, Mohammad Farooque (Frontiers in Veterinary Science, 2023)
Abstract： Hexavalent chromium Cr (Ⅵ) is one of the most hazardous heavy metals in the environment and is toxic to living organisms causing tissue damage, disruption of the intestinal microbiota and cancer. However, there is little information on the relationship between the Cr (Ⅵ) and broiler chickens. The current study was performed to investigate the effect of Cr (VI) on growth performance, serum biochemical analysis, histopathological observations, and metabolomics analysis in broilers. Results show that Cr (Ⅵ) exposure significantly decreased the body weight (p < 0.01) and caused liver damages in broilers. With the extension of Cr (Ⅵ) action time, the liver appeared obvious pathological changes, including hepatic cord disorder, incomplete hepatocyte additionally, decreased serum biochemical indices of calcium (Ca), phosphorus (P), total protein ( TP ) , phosphatase (ALP) and globin (GLB) significantly (p<0.01). Moreover, metabolomics analysis indicated that 29 differential metabolites were identified, such as phytosphingosine, L-Serine, 12, 13-DHOME, Alpha-dimorphecolic acid, L-Methionine, L-Phenylalanine, 3-Dehydroshikimate, L-Tyrosine, and N-Acetyl-L-phenylalanine were significantly decreased under the action of Cr (Ⅵ) (p < 0.05). These 29 differential metabolites are mainly involved in 35 metabolic pathways, such as aminoacyl-tRNA biosynthesis, phenylalanine metabolism, sphingolipid and linoleic metabolism. The study revealed that exposure to Cr (VI) resulted in a decrease in growth performance and metabolism, with the hazards and toxicity in broiler chicken. The findings provided new insight and a comprehensive understanding of the relationship between Cr (VI) and broiler chickens.